3=n-(-6)

Simple and best practice solution for 3=n-(-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3=n-(-6) equation:


Simplifying
3 = n + -1(-6)

Multiply -1 * -6
3 = n + 6

Reorder the terms:
3 = 6 + n

Solving
3 = 6 + n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-1n' to each side of the equation.
3 + -1n = 6 + n + -1n

Combine like terms: n + -1n = 0
3 + -1n = 6 + 0
3 + -1n = 6

Add '-3' to each side of the equation.
3 + -3 + -1n = 6 + -3

Combine like terms: 3 + -3 = 0
0 + -1n = 6 + -3
-1n = 6 + -3

Combine like terms: 6 + -3 = 3
-1n = 3

Divide each side by '-1'.
n = -3

Simplifying
n = -3

See similar equations:

| 0.5b+4=2+3d-0.5 | | 2(-8x+5)+5x=7(x+4) | | -6x+3(3x+12)=18 | | v+(-6)=-24 | | 3x-16+3x=2+6x-18 | | .07x+.05(x-2400)=196 | | -6y-4=-5y-7 | | 2x+3(x-1)=4x-17+2x | | 12t=9(t-15) | | 10.60+106= | | r^4=1024 | | 4u^2+4u-32= | | 9=r(r-8) | | 10.60-106= | | 7-(3n-3)=2-4n | | 2(x+2)+4x=x+5 | | 7r^2-10=25 | | 7x+8=x^2 | | 9(y+9)=8y-7 | | 6b^2-11b-35=0 | | -(b+1)=10-b | | 6a+3=-3(2a-1) | | 4x-10-6x+3=5-9x-7+2x | | 1500+8x=1500+12x | | 106-21.20= | | 6p=3(t+4)-t | | 8x^2-13=-8 | | 22-(x+5)=7x-7 | | 4x-14-6x+4=6-8x-8+2x | | 3y-5=5y+4 | | 6m^2+5m-4= | | 5d-d= |

Equations solver categories